Nilai Perusahaan dalam Formula Tobin’s Q Ratio - Solikhatul Ana; Doni Teguh Wibowo (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Research on the value of companies in this Tobin's Q Ratio formula, how the level of market value equity, and the level of corporate debt in the model are able to measure the value of companies. The design of this study uses a descriptive analysis method, which is explanatory which explains the analysis in the Tobin's Q Ratio formula as a tool for company value. This study adopts the Tobin's Q Ratio model used as an analytical framework in measuring the value of non-cycliclas consumer sector manufacturing companies listed on the Indonesia Stock Exchange. The results of the study were obtained, the Q Ratio which was categorized as successful by being able to manage the company's assets to liabilities; AMRT, ICBP, CPIN, UNVR, HMSO, MYOR, and CMRY. Companies in the failed category are not able to manage the company's assets to liabilities; INDF, GGRM, and JPFA. The advantage of using the Tobin's formula is that it can summarize relevant information in making investment decisions. In this formula, a company can increase share capital if the Q ratio is high because if the Tobin's Q value is above, the company will produce a higher rate of return compared to that incurred by the cost of assets. Tobin's Q as a tool to measure the value of a company, is able to provide an overview of the fundamental aspects of the company and the market's view of the company.